Assessment of Teachers’ Job Commitment in Public Senior Secondary Schools in Sokoto State, Nigeria - Usman, Hamza Abubakar; Akinnubi, Olaolu Paul; Ayoku, Oba Baba (Pedagogik: Jurnal Pendidikan, 2024)
This study aimed to assess teachers' job commitment in public senior secondary schools in Sokoto State, Nigeria. A descriptive survey was conducted with 183 school principals from 447 schools. The researcher's instrument titled Assessment of Teachers' Job Commitment Questionnaire (ATJCQ) was used to collect data. Descriptive statistics was used to analyze the data collected for this study. The study reveals that teachers' job commitment in public senior secondary schools in Sokoto State, Nigeria is moderate. The average mean is 2.97 on the appropriate use of instructional materials, 2.99 on punctuality, and 2.83 on classroom management. Dimensions used have influenced the job commitment of teachers in public senior secondary schools in Sokoto State, Nigeria. It is recommended that teachers ensure appropriate instructional materials are used when teaching students to improve their participation in the teaching and learning process.